Investigating Students’ Creativity in Teaching Mechanics Concept with Learning Management System - G Gunawan, Ahmad Harjono, Ni Made Yeni Suranti, Lovy Herayanti (International Journal of Advanced Science and Technology, 2020)
Learning management systems (LMS) has been widely recognized as an effective platform for modern learning. LMS allows teachers to manage and monitor student activities. This article discusses the use of LMS in teaching mechanics and its effect on student creativity. This research includes development research with three stages, namely preliminary studies, design development, and model testing. The model testing stage used a quasi-experimental method with one group post-test design. The sample of this study were 21 students in a university in Mataram, Indonesia. The measured creativity includes verbal creativity, figural creativity, numerical creativity, and procedural creativity. The results showed that there were differences in students’ creativity scores in each aspect. The creativity test consists of 10 essay questions that are spread on each aspect. The results showed that there were differences in students’ creativity scores in each aspect. The highest average creativity score is in the verbal aspect, then followed by figural and numerical creativity. The lowest creativity score is on procedural aspects. Based on students’ responses, the LMS was able to meet their learning needs because it contains learning resources, learning media, worksheets, and practice questions. Keywords: Learning management system, online learning, creativity, mechanics.